Letter - Stevenson, Daniel M., Sir
042-0070-001 Telegrams: "Ambulance, Cleveden, Glasgow" Telephone: West 2470 Scottish Ambulance Unit in Spain Commandant : Miss Fernanda Jacobsen, O.B.E. 5 CLEVEDEN ROAD, GLASGOW, W.2 Chairman: Sir Daniel Stevenson. Bart.. LL.D. Committee: Ishbel, Marchioness of Aberdeen and Temair, G.B.E. The Countess of Oxford and Asquith. Sir Henry Ballantyne William Black. Esq. P. J. Dollan, Esq., Treasurer. Bailie Elger. A. Forrester-Paton, Esq. The Hon. Mrs. Forrester-Paton. Professor and Mrs. Glaister. Sir Thomas and Lady Glen-Coats. Mrs. John M. Hogg, Lenzie. Miss Fernanda Jacobsen, O.B.E. Sir John Mann. K.B.E. Sir David Mason, LL.D. David Perry, Esq. Sir Andrew H. Pettigrew, LL.D. Ralph Risk, Esq., M.C. The Rt. Hon. Sir Archibald Sinclair, Bart. M.P. Lady Swan. Professor Walton. Lady Wilson, of Uddingston. Secretary : Miss Riffkin. In affiliation with The National Joint Committee for Spanish Relief, Chairman: The Duchess of Atholl, D.B.E., M.P., LL.D. Vice-Chairmen: The Earl of Listowel Miss Eleanor Rathbone, M.P. Hon Secretaries: Mr. D.R. Grenfell, M.P. Capt. J.R.J. Macnamara, M.P. Mr. Wilfrid Roberts, M.P. Treasurer (pro tem.): Mr. Wilfrid Roberts, M.P. 4th February, 1938. Dear Sir Walter, We have had another bus presented to us and Mr. Watters has just arrived from Madrid to take delivery. We are packing it full of various essentials, medical stores and foodstuffs and have a large quantity of the latter on order subject to the wherewithal coming in to pay for them. You will therefore understand how more than grateful I am on opening your letter dated 1st but only received by second post today 4th to find in it a cheque for £250. I hope this is merely a foretaste of what may come in from others in reply to my appeal of last week. Unfortunately the whole thing may be upset by the National Joint Committee having appointed a Scottish Committee with instructions to co-ordinate and increase effort in Scotland and send all funds to London to be re-allocated in accordance with the needs of the local Organisations. So far our Unit has collected far more money than all the other Scottish Organisations put together. It will be tragic if this reorganisation plan reduces instead of increasing our resources. With renewed thanks, I am, Yours sincerely, D.M. Stevenson Sir Walter Citrine, K.B.E., Transport House, Smith Square, London, S.W.1. 292/946/42/70